Handbook of Research on Ergonomics and Product Design (2018)
Product design is an important field where ergonomics and human factors should be applied. To achieve this goal, effective strategies for process improvement must be researched and implemented. Theories, Methods, and Applications in Ergonomics and Product Design is a critical scholarly resource that provides new theories, methodologies, and applications of ergonomics and product design and redesign. Featuring a broad range of topics such as additive manufacturing, product analysis, and sustainable packing development, this book is geared towards academicians, practitioners, and researchers seeking current research on new theories, methods, and applications related to ergonomics and product design.